EFISIENSI PEMUPUKAN K DENGAN BOKASHI TINJA PADA CABAI BESAR - Widowati Widowati; Astutik Astutik; Elisabeth Nogo (Universitas Tribhuwana Tunggadewi, 2007)
Problem of feces closely related to environmental problems. Application of a proper feces handling technology is expected to lessen the negative environmental impact of feces. Objective of the research was to study the ability of feces bokashi in improving availability of soil K and K uptake by big chili. Twelve treatments comprising three levels of feces bokashi and four levels of KCl fertilizer applications were arranged in a factorial block design with there replicates. Results of the study showed that interaction of bokashi feces and KCl fertilizer influenced chili dry weight production. Application of 15 ton feces bokashi /ha combined with 350 ton KCl/ha yielded highest production of dry weight. Application KCl fertilizer significantly affected dry weight and fruit of crop. While application of feces bokashi did not significantly influence K uptake by chili, application of KCl fertilizer significantly influenced K upatek by chili. K fertilization efficiency of 133 % was obtained by application of 15 ton feces bokashi/ha combined with 350 kg KCl/ha